An Analysis of Islamophobia and the Anti-Islam Discourse: Common Themes, Parallel Narratives, and legitimate Apprehensions (American Journal of Islam and Society, 2017)
In the recent past, fear, hatred, and hostility toward Islam and Muslims inthe West have attracted increasing scholarly interest, a development that iscertainly commendable. Some important works have delved deeply intothe Western imagination and stereotyping of Islam and Muslims, amongthem John Victor Tolan’s Medieval Christian Perceptions of Islam (1996)and Saracens: Islam in the Medieval European Imagination (2002),Fredrick Quinn’s The Sum of All Heresies: The Image of Islam in WesternThought (2008), Matthew Dimmock’s Mythologies of the Prophet Muhammadin Early Modern English Culture (2013),1 and Sophia Rose Arjana’sMuslims in the Western Imagination (2015) ...